Hippocampal function is compromised in an animal model of multiple sclerosis. (19th November 2015) - Novkovic, T.; Shchyglo, O.; Gold, R.; Manahan-Vaughan, D.
Highlights: Cognitive dysfunction occurs in multiple sclerosis (MS). Experimental autoimmune encephalomyelitis (EAE) mimics MS in rodents. We studied the effects of EAE on hippocampal function. Action potential firing, LTP and spatial memory were impaired in the late, but not early, phase of EAE. Thus, hippocampal function may become compromised as MS progresses. Abstract: Multiple sclerosis (MS) is a progressive inflammatory autoimmune disease that is characterized by demyelination and axonal damage in the nervous system. One obvious consequence is a cumulative loss of muscle control. However, cognitive dysfunction affects roughly half of MS sufferers, sometimes already early in the disease course. Although long-term (remote) memory is typically unaffected, the ability to form new declarative memories becomes compromised. A major structure for the encoding of new declarative memories is the hippocampus. Encoding is believed to be mediated by synaptic plasticity in the form of long-term potentiation (LTP) and long-term depression (LTD) of synaptic strength. Here, in an animal model of MS we explored whether disease symptoms are accompanied by a loss of functional neuronal integrity, synaptic plasticity, or hippocampus-dependent learning ability. In mice that developed MOG35–55 -induced experimental autoimmune encephalomyelitis (EAE), passive properties of CA1 pyramidal neurons were unaffected, although the ability to fire action potentials became reduced in the late phase of EAE. LTP remained normal in the early phase of MOG35–55 -induced EAE. However, in the late phase, LTP was impaired and LTP-related spatial memory was impaired. In contrast, LTD and hippocampus-dependent object recognition memory were unaffected. These data suggest that in an animal model of MS hippocampal function becomes compromised as the disease progresses.